Individual and demographic responses of the palm Brahea aculeata to browsing and leaf harvesting in a tropical dry forest of Northwestern Mexico - Franceli Macedo-Santana; Christa Horn; Tamara Ticktin; María Teresa Pulido Silva; Bryan A. Endress; Leonel Lopez-Toledo (PeerJ)
Background The leaves of many palm species represent important non-timber forest products (NTFPs), which may be intensively harvested by local people in many tropical areas. Additionally, in some regions livestock graze in natural forests, and they may browse on palm leaves, especially during the dry season. Thus, harvesting and browsing can result in the loss of leaf area of individual palms, which may alter functional traits of individuals and change demographic patterns of populations. Currently, there are few studies that analyze the effects of multiple disturbances on these traits. The goals of this study were to evaluate the effects of browsing, leaf harvesting and the interaction between these two factors on individual traits and demographic patterns of the Brahea aculeata palm in northwestern Mexico. Methods A browsing and leaf harvesting experiment was conducted on natural populations of the species. Individuals were subjected to different harvesting intensities and the presence or absence of cattle. Annual censuses were conducted from 2011 to 2014, and individual traits (leaf length, petiole length, and leaf production) and vital rates were monitored. Results At the individual level, the analyzed traits mostly increased as function of leaf harvest and browing, especially during the first two years. Palms experiencing leaf harvesting and browsing had 1.5 to 6.0 times higher levels of leaf production than control palms, especially juveniles and small adults. At the demographic level, the effects of browsing and leaf harvest were low or null, since survival was not affected by them. Browsing positively affected the growth of B. aculeata individuals in the first 2 years, while leaf harvesting had a negative effect in year three. There was a positive relationship between the probability of reproduction and leaf harvest; however, high leaf harvest resulted in two to three times fewer fruits produced. After 3 years of experimental management, multiple of the analyzed attributes decreased, suggesting that B. aculeata changed patterns of resource allocation. Based on our results, B. aculeata can be considered a species that tolerates high levels of defoliation and browsing for 2 years, but not likely longer. This study contributes basic ecological information useful for the conservation and management of B. aculeata, but overall it also highlights that different anthropogenic activities may act as drivers affecting the functional response and demography of NTFP species and they should be considered for the long-term integral management of these species.